PROSES PEMBELAJARAN DARING DI PAUD NONFORMAL PADA MASA COVID -19 - Lulu Yuliani; Nastiti Novitasari; Adang Danial (Comm-Edu (Community Education Journal), 2022)
This research was conducted to find out the online learning process at NonformalPAUD (Study on PlayGroup (Kober) Nurul Anwar Tawang District of Tasikmalaya City). This research uses a qualitative approach to obtain in-depth data, a data that contains meaning. Researchers conducted observations and looked for descriptive data in the form of written or oral words from respondents who were tapped via phone and WhatpApp to collect data from Nonformal PAUD Tutors, Managers and Parents. Based on the results of research that the Online Learning Process in PAUD Nonformal Nurul Anwar Play Group is carried out through three stages of learning planning, learning implementation, and learning evaluation. The online learning process using the WhatsApp application that is incorporated in the WhatsApp Group, Tutors carry out the preparation of learning planning that makes a Daily Learning Implementation Plan (RPPH) and a weekly learning implementation plan (RPPM). Tutors carry out online learning activities that are carried out include learning opening activities, core learning activities, learning conclusions. Furthermore, tutors carry out online learning evaluation stages that contain assessments of the results of children's activities sent through video, photos, and voicenotes and are used as the basis for daily, weekly, monthly, and end-of-semester assessments.